Prevalence and Clinical Relevance of Antiphospholipid Antibodies in Ischemic Stroke: A Systematic Review and Meta-Analysis - Nathan W. Watson; Syed Bukhari; Sina Rashedi; Mariana Pfeferman; Francisco Ujueta; Bassil Bacare; Brittany N. Weber; Mehrdad Zarghami; Yogendra Kanthi; Eric A. Secemsky; Jean M. Connors; Geoffrey D. Barnes; et al. (Stroke, 2026)
BACKGROUND: Antiphospholipid antibodies (aPL) are associated with an increased risk of thrombosis. However, individual studies have reported conflicting findings regarding the prevalence of aPL in patients with ischemic stroke and their association with first or recurrent events. METHODS: Systematic searches of PubMed and Embase through May 13, 2025 were conducted to identify case-control, cohort, or cross-sectional studies investigating 3 questions related to aPL seropositivity (defined as positivity for either immunoglobulin G/immunoglobulin M anticardiolipin antibody, immunoglobulin G/immunoglobulin M anti-β2 glycoprotein I antibody, or a lupus anticoagulant): (1) the prevalence of aPL seropositivity among individuals with ischemic stroke; (2) the association between aPL seropositivity and the risk of first ischemic stroke; and (3) the association between aPL seropositivity and the risk of recurrent ischemic stroke. Random-effects models with inverse weighting were used to calculate pooled prevalences and odds ratios (OR) with 95% CIs. Risk of bias was assessed using the ROBINS-I tool. RESULTS: A total of 52 studies were included (40 case-control, 12 cohort). The pooled prevalence of seropositivity for any aPL among patients with ischemic stroke (51 studies, 9438 patients) was 19.1% (95% CI, 15.4%–23.0%; I 2 =95.8%). aPL seropositivity was associated with higher odds of first ischemic stroke (43 studies, 19 097 patients; OR, 2.93 [95% CI, 2.31–3.73]; I 2 =68.7%). The strongest associations were for lupus anticoagulant (OR, 6.69 [95% CI, 2.94–15.2]; I 2 =92.6%) and immunoglobulin G anticardiolipin antibody (OR, 2.56 [95% CI, 1.96–3.35]; I 2 =92.5%). The odds of recurrent ischemic stroke among patients with versus without any aPL seropositivity were not significantly different (OR, 1.20 [95% CI, 0.87–1.67]; 9 studies, 2873 patients, I 2 =11.4%). CONCLUSIONS: Seropositivity for any aPL was present in nearly 1-in-5 patients with ischemic stroke and was associated with increased odds of ischemic stroke at presentation.